Aroma volatiles production during fruit ripening of 'Kensington Pride' mango - Lalel, H.; Singh, Zora; Tan, S. (2003)
'Kensington Pride' mango aroma volatile compounds emitted during ripening were studied using headspace solid-phase microextraction as a sampling method and gas chromatography with a flame ionisation detector as well as gas chromatography mass spectrophotometry for analysis. Fruit were ripe on the seventh day of the ripening period, which corresponded to the fruit being eating soft and a skin colour that was 75% yellow. Ethylene production and respiration reached a peak on the fourth day of ripening. Most of the fatty acids increased during fruit ripening. Sixty-one aroma volatile compounds were identified, of which 35 compounds have not been reported previously in 'Kensington Pride' mango. (+)-Spathulenol and -maaliene were found for the first time in mango fruit. The most abundant group of volatile compounds was hydrocarbons, accounting for about 59% of the total identified compounds, followed by esters (20%). -Terpinolene was the major compound during the first 7 days of ripening and later ethyl octanoate became the major compound. Except for car-3-ene, the concentration of major monoterpenes increased for the first 3 or 4 days and decreased afterwards. Most of the major sesquiterpenes were intensively synthesised in the early part of the ripening process. The production of three major esters increased quite sharply during fruit ripening. It appeared that production of terpenes was parallel with production of ethylene, whilst production of esters appeared to be associated with production of fatty acids